2016
DOI: 10.1016/j.jss.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient virtual clinical encounters after complex surgery for cancer: a prospective pilot study of “TeleDischarge”

Abstract: Secure VCEs can be conducted using widely available hardware and software solutions. Although cancer patients support the introduction of mobile technology into postoperative care, further studies are needed to identify ways in which such technology can be used most effectively and efficiently to reduce barriers to recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…VC was used in home-care situations and follow-up appointments after a hospital stay. Included were VC applications in very different health situations: Follow-ups and appointments after major cancer surgery; 34 postpartum, [35][36][37] for patients having diabetes mellitus; 38 for patients with chronic illness; 39 for parents with premature infants; 40 and for children with cancer. 41 The literature review matrix, shown in Table 1, was guided by Mallow et al 42 and includes the names of the authors and publication years, country, aim, design, participants, and results.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…VC was used in home-care situations and follow-up appointments after a hospital stay. Included were VC applications in very different health situations: Follow-ups and appointments after major cancer surgery; 34 postpartum, [35][36][37] for patients having diabetes mellitus; 38 for patients with chronic illness; 39 for parents with premature infants; 40 and for children with cancer. 41 The literature review matrix, shown in Table 1, was guided by Mallow et al 42 and includes the names of the authors and publication years, country, aim, design, participants, and results.…”
Section: Reviewmentioning
confidence: 99%
“…A rapid development in the technology field showed growing use of online equipment. 34 In 2008 a study showed blurred video problems for the first few minutes of VC, due to simultaneously use of other internet devices 41 . Web access connections could still be problematic.…”
Section: Subcategory "Access and Equipment"mentioning
confidence: 99%
“…The use of telemedicine technology after surgery has been explored for a variety of surgical procedures and may support the implementation of short‐stay colorectal resection. Telemedicine allows remote monitoring of patients after discharge, to allow prompt intervention for complications, and provides an additional means of communication between provider and patient.…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of literature pertaining to telemedicine consultation in the surgical outpatient setting, using various devices that are portable, but not autonomously mobile 46 – 50. Additionally, feasibility of telemedicine in the assessment of trauma patients in A&E51 and ICU patients23 has been shown.…”
Section: Discussionmentioning
confidence: 99%